Improving The Quality of Procurement Process Through Lean Six Sigma In The Indonesian Public Rail Transport Company - Alfatiani, Nitra; Cahyadi, Eko Ruddy; Mulyati , Heti (Riviera Publishing, 2025)
X, a public railway transportation company, is experiencing challenges in its procurement process, including frequent delays and failures. To support timely project execution and optimal budget utilization, this study applies the Lean Six Sigma methodology through the DMAIC (Define, Measure, Analyze, Improve, Control) framework to analyze inefficiencies and propose improvements. The Define phase identifies key procurement issues and customer expectations; the Measure phase calculates the current sigma level (3.33) and highlights problem patterns; the Analyze phase explores root causes using fishbone diagrams and 5 Whys; the Improve phase presents 13 actionable recommendations; and the Control phase outlines a plan to sustain improvements. The primary issue identified is a 16.81% procurement failure rate, mainly due to bids exceeding the Owner’s Estimate and the absence of qualified vendors. Cost-benefit analysis confirms the feasibility of improvements, showing a Net Present Value (NPV) of IDR 770,512,859, a Benefit-Cost Ratio (BCR) of 1.557, an Internal Rate of Return (IRR) of 108%, and a Payback Period of 1 year. These findings support the implementation of targeted process enhancements to improve procurement performance at PT. X.